Surgical techniques for the removal of Essure® microinserts: a literature review on current practice. (3rd September 2021) - Chene, G.; Cerruto, E.; Merviel, P.; Agostini, A.; Crochet, P.; Giraudet, G.; Capmas, P.; Fernandez, H.; Graesslin, O.
Abstract: Purpose: To evaluate the different techniques for Essure ® microinserts removal and to assess the risk of fracture of the device and the intra- and post-operative complications in relation to surgical technique variants Methods: Electronic search in Medline, Scopus and Embase databases using the following keywords: Essure; Essure removal; Essure surgical technique. Results: Out of 95 articles in the initial database, 17 studies were eligible for inclusion in our literature review. Several surgical techniques have been described in which the most frequent were laparoscopic salpingectomy (LS), laparoscopic cornuectomy (LC), laparoscopic or vaginal hysterectomy (LH, VH) with en-bloc salpingectomy. There were more fractures of the device with the LS procedure (6.25%) followed by the LC technique (2.77%), while there was no fracture with hysterectomy. However, peri-and post-operative complications were more severe and frequent with hysterectomy in comparison with the LC and LS procedures (respectively 8.1% Clavien Dindo grade 3 for the hysterectomy group, 1.11% for the LC procedure and 0.69% for the LS technique). Conclusion: Due to the lack of standardised surgical treatment guidelines, a system of care networks for symptomatic patients with adverse effects related to Essure ® headed by specialised centres may offer a suitable and high-quality management with the appropriate removal techniques within two objectives: limiting the risk of fracture (with an en-bloc removal of the Essure ® microinserts) and avoiding intra- and post-operative complications.